PENGARUH PRODUK, LOKASI DAN LAYANAN TERHADAP KEPUASAN PELANGGAN SERTA KEPUASAN PELANGGA TERHADAP NIAT PEMBELIAN ULANG - Cahyadi, Apdian; Sumarsono, Sumarsono (Faculty of Economics and Business Universitas Jenderal Soedirman, 2013)
The purpose of this study to analyze the influence of service, location, product and customer satisfaction impact customer satisfaction on repurchase intention. Analysis tool that is used Stuctural Equation Model (SEM). The results of this study is the service, location and product positive effect on customer satisfaction and customer satisfaction has a positive effect on repurchase intention.